PENGARUH KEADILAN, SISTEM PERPAJAKAN, DAN KEMUNGKINAN TERDETEKSINYA KECURANGAN TERHADAP PERSEPSI WAJIB PAJAK MENGENAI ETIKA PENGGELAPAN PAJAK (TAX EVASION) - Pulungan, Riski Hamdani; Taufik, Taufeni; -, Julita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to examine and analyze the effect of justice, taxation system, and the possibility of detection of fraud against the taxpayer's perception of ethics of tax evasion. The population in this study is the individual taxpayer listed on KPP Pratama Senapelan Pekanbaru. The sampling technique using convenience sampling method and determination of sample size in this study was calculated by the formula slovin obtained by 100 respondents. The data of this research using primary data directly through a questionnaire and analyzed using SPSS 20. The data were analyzed to test the hypothesis using multiple linear regression analysis approach. The results of this study show that first, justice affect the taxpayer's perception regarding the ethics of tax evasion. Second, the tax system affects the taxpayer's perception regarding the ethics of tax evasion. Third, the possibility of detection of fraud affect the taxpayer's perception regarding the ethics of tax evasionKeywords: justice, taxation system, the possibility of fraud detection, tax evasion.